(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
In underground mining of deep horizons, rock pressure can manifest itself in any form, posing a serious threat to the lives of workers, disrupting the normal course of mining operations and reducing the efficiency of mining. The solution to the problem of controlling rock pressure is becoming very important for underground mines leading the development of vein deposits at a depth of more than 250 m. The aim of the work is to develop and substantiate technological schemes that ensure safe and efficient development of deposits in difficult mining and mechanical conditions. In the work, the factors of redistribution and dangerous concentration of stresses in the developed ore massif are established, methods of rock mass management in difficult geomechanical conditions are studied, their advantages and disadvantages are revealed. It has been determined that the sublevel development system with the combined use of existing methods for controlling rock pressure and the use of self-propelled equipment in the production processes of this system is currently one of the progressive ones in improving and expanding the scope of its application. On the example of the Zarmitan gold ore zone, the variants of technological schemes of a sublevel mining system combining a combination of different methods of controlling rock pressure, allowing minimizing the disadvantages of one using the advantages of others, are considered. sublevel mining systems with artificial supporting retaining pillars of polygonal shape and sublevel development systems with artificial supporting retaining columnar pillars are proposed, which allow reducing the loss of ore in intervening pillars, ceilings and secondary dilution. In addition, artificial pillars, perceiving compressive-tensile stresses to themselves, prevent their concentrations and create safe conditions for working out adjacent and lower horizons